Possessor extraction and categorical subject in Tseltalan - Aissen, Judith; Polian, Gilles (Natural language and linguistic theory, 2025)
The Tseltalan (Mayan) languages, Tsotsil and Tseltal, have two options for extracting the possessor in wh-questions. Wh-movement can either move the entire possessive phrase (‘pied piping’) or it can move the possessor alone, stranding the possessum. Each option is associated with restrictions related to the specificity of the possessum: stranding is possible only when the possessum is non-specific, pied-piping only when it is specific. We focus primarily on the former restriction. Earlier work on Tsotsil, and the related language, Ch’ol, analyzed the derivation with stranding as involving subextraction, i.e., extraction of an internal possessor. We argue that subextraction is not possible at all in Tseltalan and that therefore only an external possessor can be extracted without pied-piping. It is fairly clear that in transitive clauses, possessors of the internal argument are extracted as external possessors, not internal ones, as they extract only as applied objects in an applicative construction. We extend this analysis to unaccusative clauses, arguing that the possessor of the internal argument in an unaccusative clause, as well as to the possessor within certain prepositional phrases, extracts from an external position. We identify this position as Specifier of TP and propose that the phrase which occupies it is interpreted as the subject of a categorical judgment (Kuroda 1972, among others). This analysis accounts for specificity effects in possessor extraction and illuminates issues related to word order, predicative possession, experiential collocations, and the nature of ’topic’ positions in Mayan.